ANALISIS KETERAMPILAN DASAR MENGAJAR DALAM PEMBELAJARAN BAHASA INDONESIA DI SD/MI - Maulida, Wildatul; Mukri, Rusdiono (Prodi PGMI IAI Sahid, 2025)
This research aims to describe teaching skills in learning Indonesian by providing skills in the learning process, because teachers often deliver material only using the lecture method without providing other skills in the learning process. Skills in learning Indonesian can be done by using the explanation method, not by the lecture method, but by using the skills possessed by a teacher or by using media which is used as a supporting tool for students with the aim of achieving predetermined learning goals. Thus, the better the teacher's way of delivering the material, the easier it will be for students to improve their understanding. This research uses a type of literature review research or library research. The literature review was carried out by collecting references consisting of several previous studies, which were then compared to draw conclusions.